Predictors of outcome among young adult patients with anorexia nervosa in a randomised controlled trial. (9th August 2018) - Nyman‐Carlsson, Erika; Birgegård, Andreas; Engström, Ingemar; Gustafsson, Sanna Aila; Nevonen, Lauri
Abstract: Objective: The prognosis in cases of anorexia nervosa (AN) is unsatisfactory, and it is therefore important to examine pretreatment predictors of outcome. Methods: Female AN patients ( N  = 74) included in a randomised controlled trial receiving individual cognitive behavioural therapy (CBT) or family‐based treatment (FBT) were included. Predictors of the outcome were explored using pretreatment eating disorder psychopathology. Results: In the CBT group, lower levels of emotional dysregulation and greater deficits in identifying and coping with inner states were predictors of weight increase, explaining 37.7% of the variance. In the FBT group, lower interoceptive deficits predicted an increase in weight (explaining 17.7% of the variance), whereas bulimic behaviour (32.4%) and problems with emotional regulation (23.3%) were predictors of increased diagnostic symptoms. Conclusions: Bulimic symptoms and the ability to identify and cope with emotional states appear to be important aspects that should be addressed in the treatment of young adult patients with AN.